2021
DOI: 10.26740/jekobi.v4n3.p215-229
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Halal Knowledge, Islamic Religiosity dan Kualitas Produk terhadap Keputusan Pembelian Produk Wardah

Abstract: Kosmetik the main needs of society in countries that are predominantly Muslim, Wardah is a brand of cosmetics brand in the first country to include halal label on its products, and is also known by some communities in Indonesia as products that demonstrate its existence, safe, high quality and also halal. This study aims to determine the effect of halal knowledge, religiosity and product quality on purchasing decisions of wardah cosmetics on Muslim consumers in Surabaya. The sampling technique used is a non-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(8 reference statements)
2
0
0
3
Order By: Relevance
“…These findings do not align with the research conducted by Khan et al (2020), which proposed that consumers equipped with halal literacy be more aware of the importance of purchasing halal products, resulting in a preference for halal-branded food. However, these results coincide with the research carried out by Achmad & Fikriyah (2021), indicating that students' decisions to buy halal-certified products are not significantly swayed by their level 319 p-ISSN: 2503-4235 of halal knowledge. Instead, it was influenced by their knowledge of the product (Nurhayati & Hendar, 2019;Rachmawati et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings do not align with the research conducted by Khan et al (2020), which proposed that consumers equipped with halal literacy be more aware of the importance of purchasing halal products, resulting in a preference for halal-branded food. However, these results coincide with the research carried out by Achmad & Fikriyah (2021), indicating that students' decisions to buy halal-certified products are not significantly swayed by their level 319 p-ISSN: 2503-4235 of halal knowledge. Instead, it was influenced by their knowledge of the product (Nurhayati & Hendar, 2019;Rachmawati et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, it can be inferred that halal knowledge holds the potential to exert a positive influence on the decision-making process of students when considering the purchase of halal-certified products. This supposition aligns with previous research, which demonstrated that product quality indeed yields a positive influence on purchasing decisions (Achmad & Fikriyah, 2021). Drawing from this contextual foundation, the ensuing hypothesis can be framed as follows:…”
Section: Hypotheses Developmentsupporting
confidence: 79%
“…Religiusitas adalah penghayatan dan keyakinan agama seseorang terhadap adanya sang pencipta yang kemudian diwujudkan dengan mematuhi segala perintah dan menjauhi larangannya dengan rasa ikhlas dari hati dan dengan seluruh jiwa dan raganya [9]. Religiusitas berpengaruh pada keputusan pembelian yang dilakukan oleh konsumen dengan hasil 67% dari 100 responden [10], penelitian yang dilakukan oleh [11] membuktikan bahwa religiusitas tidak berpengaruh secara signifikan terhadap keputusan pembelian, sedangkan pada penelitian yang dilakukan oleh [ 12] membuktikan bahwa konsumen dengan pemahaman religiusitas yang tinggi berpengaruh terhadap keputusan pembelian.…”
Section: Pendahuluanunclassified
“…Komunikasi pemasaran adalah proses yang dilakukan oleh perusahaan di mana beberapa elemen periklanan dan kegiatan pemasaran lainnya dikoordinasikan sedemikian rupa sehingga menciptakan komunikasi dengan konsumen perusahaan. (Arjunita et al, 2021) Dalam dunia media massa dan media cetak banyak sekali fungsinya sebagai sarana untuk menawarkan produknya. Karena media massa dan media cetak bersifat global, banyak pengguna media online yang berasal dari dalam maupun luar negeri, banyak ide yang muncul untuk berkomunikasi dan menawarkan produknya di Internet.…”
Section: Pendahuluanunclassified